2018
DOI: 10.1108/pr-05-2017-0165
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the link between socially responsible human resource management and competitive performance in SMEs

Abstract: Purpose Regardless of the noteworthy growth in research and practice associating corporate social responsibility (CSR) with human resource management, little has been written in regard to one major dimension of CSR in small- and medium-sized enterprises (SMEs), as CSR policies and practices are directed toward employees. The purpose of this paper is to develop and test a conceptual framework connecting socially responsible human resource management (SRHRM) to competitive performance that fits small business. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 97 publications
(165 reference statements)
3
60
0
1
Order By: Relevance
“…In this meaning, Torres, Ferraz, and Santos‐Rodrigues () posit that knowledge assets and organizational capabilities can foster business growth and sustainable competitive advantage. Lechuga Sancho, Martinez‐Martinez, Larran Jorge, and Herrera Madueno () show the direct contribution of socially responsible human resource management on competitive performance and the significant effect of employees' commitment and relational marketing. Upstill‐Goddard, Glass, Dainty, and Nicholson (), following the case study approach, understand that strong communication channels and commitment to training programs increase the sustainability standards implementation; nevertheless, they also maintain that SMEs tend only to approach to these standards if they see immediate financial benefits from their implementation.…”
Section: Discussion Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meaning, Torres, Ferraz, and Santos‐Rodrigues () posit that knowledge assets and organizational capabilities can foster business growth and sustainable competitive advantage. Lechuga Sancho, Martinez‐Martinez, Larran Jorge, and Herrera Madueno () show the direct contribution of socially responsible human resource management on competitive performance and the significant effect of employees' commitment and relational marketing. Upstill‐Goddard, Glass, Dainty, and Nicholson (), following the case study approach, understand that strong communication channels and commitment to training programs increase the sustainability standards implementation; nevertheless, they also maintain that SMEs tend only to approach to these standards if they see immediate financial benefits from their implementation.…”
Section: Discussion Of Clustersmentioning
confidence: 99%
“…posit that knowledge assets and organizational capabilities can foster business growth and sustainable competitive advantage Lechuga Sancho, Martinez- Martinez, Larran Jorge, and Herrera Madueno (2018). show the direct contribution of socially responsible human resource management on competitive performance and the significant effect of employees' commitment and relational marketing.…”
mentioning
confidence: 99%
“…Such HRM practices help to engage employees in CSR activities and gradually transform employee responsibility awareness into organizational competitiveness and sustainable development. Indeed, evidence has shown that SRHRM has pronounced effects in promoting positive employee outcomes, such as commitment [3], task performance, organizational citizenship behavior (OCB) [4], employee support for external CSR initiatives [5], and competitive performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Shen and Benson [66] highlighted the mediation role that employee commitment plays between SR-HRM and task performance. In that sense, Lechuga Sancho et al [91] also considered that employee's commitment positively mediates the relationship between SR-HRM and the performance of small and medium enterprises. López-Fernández et al [23] studied the influence of employees' perceptions toward SR-HRM on employee commitment.…”
Section: Sub-period 2017-2019mentioning
confidence: 99%